4th Industrial Revolution and TVET: The Relevance of Entrepreneurship Education for Development - Salman Shabbir, Muhammad; Arshad Mahmood, Mohd Anuar Arshad,; Ali Sulaiman, Mohammed Ali Bait (Opción, 2019)
The scope of the study is to highlight the challenges for graduates’ students in the 4th industrial revolution via comparative qualitative research methods. As a result, the Technical and Vocational Education and Training (TVET) institutions need to adjust the implementation method of their education and training based on science and technology by offering demand-driven courses, especially in closing the competency gap with the main players of the fourth industrial revolution industry. In conclusion, the TVET institutions need to adjust the implementation method of their education and training based on science and technology by offering demand-driven courses.